The impact of retailtainment on purchase intentions - Tiago, Mafalda dos Santos (2021)
Entertainment in retail – retailtainment - has been taking the retail industry by storm in the last twenty years. Professionals in this area have understood that the right use of decoration, lights, sound, scents, unique experiences and entertainment options influences the customer’s mood, which in turn can influence their purchase intentions. The main goal of this dissertation is to understand if retailtainment causes a positive impact on customers’ purchase intentions, specifically in supermarket purchases. The developed hypotheses intend to test the effect of entertainment frequency – permanent and special or temporary – and the level of arousal – low and high – on three variables: customer satisfaction, store image and retailer loyalty. Finally, it is intended to measure the effect of these variables on purchase intentions with low-involvement – the customer quickly chooses the product to buy and there are no costs when he changes the chosen brand or supplier. Thus, an online questionnaire was designed and shared in order to collect data on the experiences of participants in their last visit to the supermarket. The survey aims to understand current views on supermarket entertainment and what improvements can be made in this regard. The collected data was analysed in the SPSS program. The main conclusions allow us to verify the similarities and differences between the effect of entertainment in malls and supermarkets and represent relevant information for food retail professionals.